Efektivitas Edukasi Gizi Pada Pengetahuan Terkait Anemia dan Kadar Hemoglobin Remaja Putri Usia 12-19 Tahun: Tinjauan Sistematis dan Meta Analisis: Effectiveness of Nutrition Education on Knowledge of Anemia and Hemoglobin Level in Female Adolescents Aged 12-19 Years: a Systematic Reviews and Meta-Analysis - Kamila Dwi Febrianti; Wilis Cahyaning Ayu; Yusrita Anidha; Trias Mahmudiono (Universitas Airlangga, 2023)
Background: Anemia is a common health problem among adolescents that needs to be resolved immediately. It is estimated that more than 50% of female adolescents aged 12-15 years have anemia. Some of the anemia's effects on adolescents include stunted growth, decreased learning ability, and susceptibility to infectious diseases. Objectives: To identify evidence for nutrition education's effectiveness on anemia knowledge and hemoglobin levels in female adolescents aged 12 to 19. Methods: Using study eligibility criteria, three electronic databases (Scopus, Science Direct, and Pubmed) were searched within five years for relevant articles. Review Manager (RevMan) version 5.4.1 was used to analyze the research findings. Results: Based on the results, there was no significant relationship between education and anemia knowledge in the control and treatment groups (p<0.05). Neither group also had a significant relationship between nutrition education and Hb concentration. However, the Active, Creative, Effective, and Fun Learning or Pembelajaran Aktif, Kreatif, Efektif, dan Menyenangkan (PAKEM) program approach impacted adolescent anemia knowledge. The mean difference value of 0, which indicates the intervention group is more effective than the control group, presented significant results. The estimated effect can be seen in the forest plot image to the left of the vertical line. Conclusions: Based on the meta-analysis, the PAKEM method is a nutritional education method that provides significant results on female adolescents' knowledge regarding anemia and Fe tablet consumption. However, the nutritional education method did not affect hemoglobin levels.